ANALISIS STRUKTUR MODAL PERUSAHAAN AKUISITOR SEBELUM DAN SETELAH MELAKUKAN AKUISISI SERTA PENGARUHNYA TERHADAP HARGA SAHAM PERUSAHAAN - - Haryati; Evaliati Amaniyah; Prasetyo Nugroho (Universitas Trunojoyo Madura, 2015)
The purpose of the study is to determine differences of capital structure on acquirer company before and after conducting acquisition and to determine the influence of longterm debt to asset ratio and equity to asset ratio to company’s stock price before and after conducting acquisition. Paired sample T-test is used to analize differences of capital structure before and after conducting acquisition, while multiple linear regression is used for determining the effect of company capital structure to company’s stock price before and after conducting acquisition. Based on purposive sampling technique, it is obtained 30 companies as samples in this study. The results of this study are longterm debt to asset ratio shows no differences before and after conducting acquisition. It is shown by the significance value of 0,287 lebih dari 0,05, while the equity to asset ratio shows no differences which is shown by the significance value of 0,019 kurang dari 0,05. Based on F-test, longterm debt to asset ratio and equity to asset ratio before and after acquisition indicates don’t have simultaneous influence on company stock price. The result of t-test indicates that both variable don’t have partial influence on company stock price before and after acquisition.